The Benefits of High-Intensity Interval Training on Cognition and Blood Pressure in Older Adults With Hypertension and Subjective Cognitive Decline: Results From the Heart & Mind Study - Boa Sorte Silva, Narlon C.; Petrella, Andrea F. M.; Christopher, Nathan; Marriott, Catherine F. S.; Gill, Dawn P.; Owen, Adrian M.; Petrella, Robert J. (Frontiers in Aging Neuroscience, 2021)
Background: The impact of exercise on cognition in older adults with hypertension and subjective cognitive decline (SCD) is unclear. Objectives: We determined the influence of high-intensity interval training (HIIT) combined with mind-motor training on cognition and systolic blood pressure (BP) in older adults with hypertension and SCD. Methods: We randomized 128 community-dwelling older adults [age mean (SD): 71.1 (6.7), 47.7% females] with history of hypertension and SCD to either HIIT or a moderate-intensity continuous training (MCT) group. Both groups received 15 min of mind-motor training followed by 45 min of either HIIT or MCT. Participants exercised in total 60 min/day, 3 days/week for 6 months. We assessed changes in global cognitive functioning (GCF), Trail-Making Test (TMT), systolic and diastolic BP, and cardiorespiratory fitness. Results: Participants in both groups improved diastolic BP [F(1, 87.32) = 4.392, p = 0.039], with greatest effect within the HIIT group [estimated mean change (95% CI): −2.64 mmHg, (−4.79 to −0.48), p = 0.017], but no between-group differences were noted (p = 0.17). Both groups also improved cardiorespiratory fitness [F(1, 69) = 34.795, p < 0.001], and TMT A [F(1, 81.51) = 26.871, p < 0.001] and B [F(1, 79.49) = 23.107, p < 0.001]. There were, however, no within- or between-group differences in GCF and systolic BP at follow-up. Conclusion: Despite improvements in cardiorespiratory fitness, exercise of high- or moderate-intensity, combined with mind-motor training, did not improve GCF or systolic BP in individuals with hypertension and SCD. Clinical Trial Registration:ClinicalTrials.gov (NCT03545958).